Analisis In Silico Potensi Minyak Kedelai (Glycine max) dalam Terapi Dermatitis Atopik - Primadhanty. R. S. Bhadra; Mardiana; Ahmad Fiqri; Ummi Rinandari; Didik H. Utomo; Muhammad Eko Irawanto (MEDICINUS, 2021)
Soybean oil contains various bioactive phytochemicals such as phenolic acids, flavonoids, isoflavones, saponins, phytosterols and sphingolipids which might give benefit in the treatment of atopic dermatitis (AD). This study aimed to evaluate the soybean oil compounds using computational in silico analysis for the treatment of atopic dermatitis. The active compounds of soybean oil were extracted from the KNApSAcK database. Results showed that soybean oil might possess some potential bioactivity such as immunosuppressant, antiinflammatory, improves skin barrier function, antieczema and histamine inhibitor. The highest potential bioactivity of soybean oil was as antiinflammatory, with an average value of probable to be active (Pa) 0.684; while the high potency active compound is alpha-tocopherol (Pa: 0.956).